THE GAME AS A PEDAGOGICAL STRATEGY TO STRENGTHEN READING COMPREHENSION IN ELEMENTARY SCHOOL CHILDREN OF THE EUSTORGIO COLMENARES BAPTISTA SCHOOL - Karina Tarazona Romero (DIALÉCTICA, 2025)
Education is the master organ to guide the progress and development of a nation, which is why it is necessary to be in constant evaluation and of course reviewing that should go hand in hand with everything that is appearing; as with technological advances; where artificial intelligence has taken over the vast majority of the processes that occur in the education system; such as teaching, learning, evaluation; among others. From there emerges the following general objective: To generate theoretical reflections on the game as a pedagogical strategy for the strengthening of reading comprehension in primary school children of the Eustorgio Colmenares Baptista School in the city of Cúcuta. The methodology used is a qualitative research, using the interpretative paradigm through the hermeneutic method; with the use of the documentary analysis technique; which leads to a systematization of the information; taking into account that we worked with search engines such as SCOPUS, Web of Sciencie and Sciencedirect; filtering documents from the last five years 2020 - 2024. This resulted in a systematic review that led to the conclusion that games, gamification, and playfulness are strategies that contribute to strengthen reading comprehension and at the same time lay the solid foundations for quality education and training in primary education.